Malpractice claims after antireflux surgery and paraesophageal hernia repair : a population-based analysis - Nurminen Nelli M. J.; Järvinen Tommi K. M.; Kytö Ville J.; Salo Silja A. S.; Egan Caitlin E.; Andersson Saana E.; Räsänen Jari V.; Ilonen Ilkka K. P. (Springer, 2025)
Background
The complication rate of modern antireflux surgery or paraesophageal hernia repair is unknown, and previous estimates have been extrapolated from institutional cohorts.
Methods
A population-based retrospective cohort study of patient injury cases involving antireflux surgery and paraesophageal hernia repair from the Finnish National Patient Injury Centre (PIC) register between Jan 2010 and Dec 2020. Additionally, the baseline data of all the patients who underwent antireflux and paraesophageal hernia operations between Jan 2010 and Dec 2018 were collected from the Finnish national care register.
Results
During the study period, 5734 operations were performed, and the mean age of the patients was 54.9 ± 14.7 years, with 59.3% (n = 3402) being women. Out of all operations, 341 (5.9%) were revision antireflux or paraesophageal hernia repair procedures. Antireflux surgery was the primary operation for 79.9% (n = 4384) of patients, and paraesophageal hernia repair was the primary operation for 20.1% (n = 1101) of patients. A total of 92.5% (5302) of all the operations were laparoscopic. From 2010 to 2020, 60 patient injury claims were identified, with half (50.0%) of the claims being related to paraesophageal hernia repair. One of the claims was made due to an injury that resulted in a patient's death (1.7%). The mean Comprehensive Complication Index scores were 35.9 (± 20.7) and 47.6 (± 20.8) (p = 0.033) for antireflux surgery and paraesophageal hernia repair, respectively. Eleven (18.3%) of the claims pertained to redo surgery.
Conclusions
The rate of antireflux surgery has diminished and the rate of paraesophageal hernia repair has risen in Finland during the era of minimally invasive surgery. Claims to the PIC remain rare, but claims regarding paraesophageal hernia repairs and redo surgery are overrepresented. Additionally, paraesophageal hernia repair is associated with more serious complications.